Molecular alterations in skeletal muscle in rheumatoid arthritis are related to disease activity, physical inactivity, and disability. Issue 1 (December 2017) - Huffman, Kim; Jessee, Ryan; Andonian, Brian; Davis, Brittany; Narowski, Rachel; Huebner, Janet; Kraus, Virginia; McCracken, Julie; Gilmore, Brian; Tune, K.; Campbell, Milton; Koves, Timothy; et al.
Abstract Background To identify molecular alterations in skeletal muscle in rheumatoid arthritis (RA) that may contribute to ongoing disability in RA. Methods Persons with seropositive or erosive RA (n  = 51) and control subjects matched for age, gender, race, body mass index (BMI), and physical activity (n  = 51) underwent assessment of disease activity, disability, pain, physical activity and thigh muscle biopsies. Muscle tissue was used for measurement of pro-inflammatory markers, transcriptomics, and comprehensive profiling of metabolic intermediates. Groups were compared using mixed models. Bivariate associations were assessed with Spearman correlation. Results Compared to controls, patients with RA had 75% greater muscle concentrations of IL-6 protein (p  = 0.006). In patients with RA, muscle concentrations of inflammatory markers were positively associated (p  < 0.05 for all) with disease activity (IL-1β, IL-8), disability (IL-1β, IL-6), pain (IL-1β, TNF-α, toll-like receptor (TLR)-4), and physical inactivity (IL-1β, IL-6). Muscle cytokines were not related to corresponding systemic cytokines. Prominent among the gene sets differentially expressed in muscles in RA versus controls were those involved in skeletal muscle repair processes and glycolytic metabolism. Metabolic profiling revealed 46% higher concentrations of pyruvate in muscle in RA (p  < 0.05), and strong positive correlation between levels of amino acids involved in fibrosis (arginine, ornithine, proline, and glycine) and disability (p  < 0.05). Conclusion RA is accompanied by broad-ranging molecular alterations in skeletal muscle. Analysis of inflammatory markers, gene expression, and metabolic intermediates linked disease-related disruptions in muscle inflammatory signaling, remodeling, and metabolic programming to physical inactivity and disability. Thus, skeletal muscle dysfunction might contribute to a viscous cycle of RA disease activity, physical inactivity, and disability.